Proofreading: Avoiding Mistake in Writing Process - Siti Arisah; Testiana Deni W; Dodi Mulyadi (Proceedings Series on Social Sciences & Humanities, 2024)
Proofreading is an important stage in the writing process that is often overlooked. This article illustrates the importance of proofreading in ensuring good quality writing. With examples of grammatical, spelling, and structural errors, we highlight the impact these errors have on understanding and portraying the author. This research method uses a qualitative method with a questionnaire given to students at the Muhammadiyah University of Semarang majoring in English Language Education. The results show that proofreading is a key element for achieving high-quality writing results.